Effect of pharmaceutically active compound omeprazole, on the corrosion of mild steel in hydrochloric acid solution - Sudheer; Quraishi M.A. (My University, 2025)
A pharmaceutically active compound Omeprazole is used as corrosion inhibitor for mild steel corrosion in 1.0 M HCl medium were analysed by electrochemical impedance spectroscopy (EIS), potentiodynamic polarization and weight loss techniques. The inhibitor showed 97% inhibition efficiency at optimum concentration. Electrochemical impedance spectroscopy techniques were also used to investigate the mechanism of corrosion inhibition. Adsorption of inhibitor molecules on the mild steel surface in hydrochloric acid obeyed the Langmuir adsorption isotherm.